A Decade of Food and Nutrition Policy in Portugal (2010-2020) - Pedro Graça; Maria João Gregório; Maria da Graça Freitas (Karger Publishers, 2020)
For the first time, in 2012, the Portuguese Government, through the National Program for the Promotion of Healthy Eating of the Directorate-General for Health, implemented a set of concerted measures for improving the dietary habits, nutritional status and health of the population. Prior to, and since 2007, several epidemiological, social and political circumstances converged, for later enabling the development of a national strategy throughout the decade 2010-2020. This was also supported by specific international guidelines, namely from the World Health Organization and the European Commission. The national strategy objectives have been: (a) To increase the knowledge about the population's food consumption, its determinants and consequences; (b) to modify the access to certain food items specially in schools, workplaces and public spaces; (c) To inform and empower individuals regarding shopping, preparation and storage of healthy foods, especially amongst those most vulnerable or with a lower income; (d) to identify and promote actions capable of encouraging a healthier diet through the integration of other societal sectors, namely agriculture, sports, environment, education, social security and local authorities; and (e) to better capacitate different professionals who, owing to their roles, may influence nutritional knowledge, attitudes and behaviors. Several actions are described, including the creation of legislation to address these objectives. It is worth noting that one of the biggest challenges to this public policy has been the interventions within the environments where people live. By knowingly being central to food choice determinants, these environmental modifications were also where the stakeholders felt the greatest tensions and difficulties, but also where there are the greatest gains to be made. Solutions to overcome these problems and other perceived difficulties have been proposed here and are considered to be some of the main lessons and achievements throughout this process.